2009
DOI: 10.1051/apido/2009068
|View full text |Cite
|
Sign up to set email alerts
|

New Asian types ofVarroa destructor:a potential new threat for world apiculture

Abstract: The invasion of the Western honey bee, Apis mellifera, by Varroa destructor is attributed to two mitochondrial haplotypes (K and J) that shifted last century from their primary host the Eastern honey bee, A. cerana, in north-east Asia. Here, mitochondrial DNA sequences (cox1, cox3, atp6 and cytb: 2700 base pairs) were obtained from mites infesting both Eastern and Western honeybees (respectively 21 and 11 colonies) from Asia including regions where the shifts first occurred. A total of eighteen haplotypes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(137 citation statements)
references
References 27 publications
(42 reference statements)
5
130
2
Order By: Relevance
“…BCC/BMC relate to VCC more closely, similar to above, suggesting that Varroa from cerana originally and still on cerana mimicked the best their host cerana bees; these three then clustered with VMC, Varroa originally from mellifera and now on cerana. Finally, the top four groups (**M) and the bottom four groups (**C) then form two common clusters, suggesting that the second host playing a much more important role than the original host, and Previous analysis has indicated mitochondrial polymorphism in Varroa [12]. As was published in that study, Varroa from Am were determined to be Korean haplotype 2 (K2) and those from Ac were Korean haplotype 3 (K3).…”
Section: Discussionmentioning
confidence: 66%
“…BCC/BMC relate to VCC more closely, similar to above, suggesting that Varroa from cerana originally and still on cerana mimicked the best their host cerana bees; these three then clustered with VMC, Varroa originally from mellifera and now on cerana. Finally, the top four groups (**M) and the bottom four groups (**C) then form two common clusters, suggesting that the second host playing a much more important role than the original host, and Previous analysis has indicated mitochondrial polymorphism in Varroa [12]. As was published in that study, Varroa from Am were determined to be Korean haplotype 2 (K2) and those from Ac were Korean haplotype 3 (K3).…”
Section: Discussionmentioning
confidence: 66%
“…It has been shown that two major mite haplotypes have spread over the world, the Japanese and the Korean haplotypes (Anderson, 2000) Each haplotype has a clonal genetic structure (Solignac et al, 2005). While it is unlikely that different Varroa haplotypes could explain the recent colony losses, two new haplotypes of Varroa destructor were recently described in A. mellifera colonies in Southeast Asia (Navajas et al, 2009). Nothing is known about their virulence on European bees outside Asia, but those haplotypes might be a new threat to consider for A. mellifera bees outside Asia.…”
Section: Varroa and Bee Host Biologymentioning
confidence: 99%
“…At least 60 years ago, it made a host switch and now parasitizes several European and African races of A. mellifera [17]. Population studies indicate that there was a genetic bottleneck associated with the host switch to A. mellifera [18][19][20]. These studies revealed a remarkable absence of heterozygosity in the Varroa populations of Europe and USA collected on A. mellifera [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These haplotypes also seem to be completely reproductively isolated from each other. Two routes of invasion of V. destructor into the Americas, and specifically into the USA, have been proposed based on the dates and places where each haplotype was first detected [18][19][20]. The J haplotype first shifted from A. cerana to A. mellifera in Japan during the last century, following the introduction of A. mellifera.…”
Section: Introductionmentioning
confidence: 99%